2012
DOI: 10.1007/s11832-012-0384-4
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tibial derotation osteotomy for torsion of the tibia: A review of 43 cases

Abstract: Purpose Persistent tibial torsion in the older child can be treated with a derotation osteotomy. Distal tibial osteotomy has been recommended due to concerns of peroneal nerve palsy, vascular injury, and compartment syndrome with a proximal tibial osteotomy. However, an osteotomy in the proximal tibia may achieve union more rapidly and skin issues, as described for distal tibial osteotomies, are less likely. This study investigates the safety and efficacy of proximal tibial derotation osteotomies. Methods We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
(32 reference statements)
2
17
0
Order By: Relevance
“…There is a controversy about the level used for a corrective osteotomy in the tibia. 1 , 10 , 14 , 15 , 17 , 22 A tibial osteotomy can be performed at either the proximal tibia, diaphysis, or distally at the supramalleolar region. 15 , 22 The proximal tibia has been used commonly in the treatment of genu valgum or varum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a controversy about the level used for a corrective osteotomy in the tibia. 1 , 10 , 14 , 15 , 17 , 22 A tibial osteotomy can be performed at either the proximal tibia, diaphysis, or distally at the supramalleolar region. 15 , 22 The proximal tibia has been used commonly in the treatment of genu valgum or varum.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 10 , 14 , 15 , 17 , 22 A tibial osteotomy can be performed at either the proximal tibia, diaphysis, or distally at the supramalleolar region. 15 , 22 The proximal tibia has been used commonly in the treatment of genu valgum or varum. 15 Recent studies have demonstrated high complication rates after proximal osteotomies, including loss of fixation, peroneal nerve injury, and compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that in patients with unilateral instability, an excessive external tibial torsion may not be the main underlying factor contributing to PF instability. A small number of complications have been reported, including nerve palsy (49,58), valgus deformity (58), distal physeal closure (59), and delayed/non-union (58)(59)(60). Complications have been typically found in less than 15% of patients which have, in some cases required revision surgery.…”
Section: De-rotation Osteotomiesmentioning
confidence: 99%
“… 2006 , Walton et al. 2012 ). Osteotomy has various disadvantages including over or undercorrection, recurrence of the deformity, difficulty in postoperative mobilization, and delayed recovery and return to daily life (Gyr et al.…”
mentioning
confidence: 99%